Rethinking Relationships - Briggs, Margaret (Victoria University of Wellington Law Review, 2018)
The Property (Relationships) Act 1976 is generally regarded as progressive and inclusive. The Act applies an equal property sharing regime to married spouses, civil union partners and de facto partners. It does not, however, recognise other sorts of close domestic relationships such as those between a parent and adult child or between siblings. This is in contrast to Australia where a number of jurisdictions have conferred relationship status on domestic relationships. This article considers whether there is a similar case to be made in New Zealand for extending property rights to people in domestic relationships.